PHYSICAL ACTIVITY DECREASES ANXIETY- RELATED BEHAVIOR IN CHRONIC PROSTATITIS/CHRONIC PELVIC PAIN SYNDROME: FUNCTIONAL BEHAVIORAL STUDY ON THE CROSSROAD OF EXPERIMENTAL EXERCISE PHYSIOLOGY AND ANDROLOGY - Šutulović, Nikola; Zubelić, Aleksa; Macut, Djuro; Vesković, Milena; Mladenović, Dušan; Rašić-Marković, Aleksandra; Stanojlović, Olivera; Hrnčić, Dragan (Medical Research, 2022)
Introduction: Chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS) is nonbacterial inflammatory syndrome, manifested by various urological symptoms, often accompanied with sexual dysfunction, and mental health issues including anxiety. Studies demonstrated beneficials effects of chronic exercise in anxiety and chronic pain treatment, but its influence on pain and anxiety in CP/CPPS have not been thoroughly investigated yet. The aim of this study was to determine the effects of chronic aerobic physical activity on anxiety-related behavior and pain sensitivity in rats with experimentally induced CP/CPPS. Material and Methods: Adult male Wistar albino rats (n=32) were randomly divided in group of physically active, which run on treadmill during 30 consecutive days (PA, 30 min/day, speed: 20 m/min; n=16) and group od sedentary, which spent the same time in treadmill off mode (SED, 30 min/day, speed: 0 m/min; n=16). After the treadmill protocol completion, depending on the type of the intraprostatic injection (0.9% NaCl or 3% λ-carrageenan) during operation, rats were randomly divided to following groups (n=8 in each group): Sham-SED (sedentary protocol and 0.9% NaCl); Sham-PA (exercise protocol and 0.9% NaCl); CP/CPPS-SED (sedentary protocol and 3% λ-carrageenan); CP/CPPS-PA (exercise protocol and 3% λ-carrageenan). To monitor on CP/CPPS development and pain dynamics, scrotal skin mechanical pain thresholds were measured by electronic von Frey aesthesiometer (evF) preoperatively: 2 and 1 day, and also postoperatively: 2nd, 3rd, and 7th day. To assess anxiety-like behavior, the animals from all groups were subjected to standard battery of three ethological tests (consisted of an open field (OF), elevated plus maze (EPM) and light/dark (L/D) test at the same postoperative time points as evF. Results: Rats which developed experimental CP/CPPS showed decreased mechanical pain threshold in the scrotal skin in all postoperative time point, in comparison to Sham group. Also, in rats with prostatitis increased anxiety-like behavior was observed in OF, EMP and L/D test, comparing to corresponding controls. Protocol of 30-days long exercise in rats with CP/CPPS led to reversion of anxiety-like behavior and increased scrotal pain threshold. Conclusion: Results of the present study showed that regular exercise on treadmill during 30 consecutive days led to amelioration of anxiety-related and pain-related behavior in rats with CP/CPPS.